Flexible Working Conditions - K. Ravi Kiran Yasaswi,; Ch. D. V. Sai Kumar,; D. Bharath Lakshman,; T. Jaswanth, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
“Flexible working conditions” is a facility to help the employees to manage their work life and personal life effectively. It provides the feasibility to work according to their choice. It may be time or place. It also improves the satisfaction levels of the employees and the productivity of the employees. It helps employers to reduce the absenteeism and turnover of the employees.
Keywords: Human Resource Management; Telecommuting; Remote Working; Freelancing; Job Sharing